1988
DOI: 10.1080/15287398809531103
|View full text |Cite
|
Sign up to set email alerts
|

Role of glutathione in the toxicity of the sesquiterpene lactones hymenoxon and helenalin

Abstract: Hymenoxon and helenalin are toxic sesquiterpene lactones present in the toxic range plants Hymenoxys odorata and Helenium microcephalum. Helenalin (25 mg/kg) or hymenoxon (30 mg/kg) administered to immature male ICR mice caused a rapid decrease in hepatic glutathione levels and were lethally toxic to greater than 60% of the animals within 6 d. L-2-Oxothiazolidine 4-carboxylate (OTC), a compound that elevates cellular glutathione levels, administered to mice 6 or 12 h before either helenalin or hymenoxon protec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

1995
1995
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 15 publications
0
10
0
Order By: Relevance
“…Likewise, helenalin dramatically reduced the tGSH pool in the HaCaT cells. Although the effects on the cellular tGSH concentrations that were obtained using the A. montana extract or helenalin seemed to conflict with the results that were observed following exposure to cadmium, other studies have described the reduction of the cellular tGSH pool by STL, including helenalin, likely through the ROS-dependent oxidization of the cysteine pool that is required for glutathione synthesis [23]. …”
Section: Resultsmentioning
confidence: 99%
“…Likewise, helenalin dramatically reduced the tGSH pool in the HaCaT cells. Although the effects on the cellular tGSH concentrations that were obtained using the A. montana extract or helenalin seemed to conflict with the results that were observed following exposure to cadmium, other studies have described the reduction of the cellular tGSH pool by STL, including helenalin, likely through the ROS-dependent oxidization of the cysteine pool that is required for glutathione synthesis [23]. …”
Section: Resultsmentioning
confidence: 99%
“…for mice of 9.85 mg/kg (5), Chapman et al (4) reported 43 mg/ kg for the same species and route of administration. Merril et al (11) found that the dose of 25 mg/kg i.p. caused the death of 60 % of tested mice.…”
Section: Resultsmentioning
confidence: 99%
“…Helenalin is a constituent of the medicinally used flower heads of Arnica species (3). Its acute toxicity, cytotoxicity (4,5), antiulcer activity (6,7) and effect on many biochemical parameters including protein synthesis, some enzymes activity (8,9) and liver glutathione level (10,11) have been investigated. There are only single reports concerning biological activity of the rest of the above mentioned lactones (1,6).…”
Section: Introductionmentioning
confidence: 99%
“…Among others, the specific metabolic targets are the thiol-bearing enzymes IMP dehydrogenase, DNA polymerase a, ribonucleoside reductase (33,36,38), elF-2 kinase, and the elongation factor eIF-3 (29,30). Furthermore, the compounds lower the cellular glutathione level (39,40).…”
Section: Biological Activities Of Arnica Sesquiterpene Lactonesmentioning
confidence: 99%
“…Acute toxicity by helenalin has been related to hepatic glutathione levels, which are rapidly depleted by very low concentrations of helenalin (39). The oral LD 5 o values of helenalin for mammals varies form 85 mg/kg for hamster to 150 mg/kg for mouse (73).…”
Section: Acute Toxicity and Contact Allergymentioning
confidence: 99%